Transformative Artistic Discourse: (Environmental Consciousness in Saudi Arabian Contemporary Art) - Dr. Rawya Mohammad Aljared (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
The evolving landscape of Middle Eastern contemporary art, particularly from Saudi Arabia, necessitates reexamining existing art historical approaches. The growing imperative drives this research to illuminate conceptual and historical narratives in regional art production. This study contends that the creative endeavors in Saudi Arabian contemporary art give rise to novel manifestations and concepts that mirror the region's environmental ethos. Supported by governmental initiatives and local art institutions, these emerging narratives explore urgent environmental concerns while resonating with ecology, energy, and urban development themes. To examine the interplay of local and international perspectives, this paper uses a qualitative methodology to conduct a review analysis of artworks showcased at prominent exhibitions such as those hosted by Noor Riyadh and Tuwaiq Sculpture. By scrutinizing these platforms, the study aims to shed light on the significant and transformative influence of governmental initiatives, biennials, art fairs, and local art institutions on shaping contemporary artistic conceptions from Saudi Arabia.